Diversity of Cellulase-Producing Filamentous Fungi From Tibet and Transcriptomic Analysis of a Superior Cellulase Producer Trichoderma harzianum LZ117 - Li, Jia-Xiang; Zhang, Fei; Jiang, Dan-Dan; Li, Jun; Wang, Feng-Lou; Zhang, Zhang; Wang, Wei; Zhao, Xin-Qing (Frontiers in Microbiology, 2020)
Filamentous fungi are widely used for producing cellulolytic enzymes to degrade lignocellulosic biomass. Microbial resources from Tibet have received great attention due to the unique geographic and climatic conditions in the Qinghai-Tibet Plateau. However, studies on cellulase producing fungal strains originated from Tibet remain very limited, and so far no studies have been focused on regulation of cellulase production of the specific strains thereof. Here, filamentous fungal strains were isolated from soil, plant, and other environments in Tibet, and cellulase-producing strains were further investigated. A total of 88 filamentous fungal strains were identified, and screening of cellulase-producing fungi revealed that 16 strains affiliated with the genera Penicillium, Trichoderma, Aspergillus and Talaromyces exhibited varying cellulolytic activities. Among these strains, T. harzianum isolate LZ117 is the most potent producer. Comparative transcriptome analysis using T. harzianum LZ117 and the control strain T. harzianum K223452 cultured on cellulose indicated an intensive modulation of gene transcription related to protein synthesis and quality control. Furthermore, transcription of xyr1 which encodes the global transcriptional activator for cellulase expression was significantly up-regulated. Transcription of cre1 and other predicted repressors controlling cellulase gene expression was decreased in T. harzianum LZ117, which may contribute to enhancing formation of primary cellulases. To our knowledge, this is the first report that the transcription landscape at the early enzyme production stage of T. harzianum was comprehensively described, and detailed analysis on modulation of transporters, regulatory proteins as well as protein synthesis and processing was presented. Our study contributes to increasing the catalog of publicly available transcriptome data from T. harzianum, and provides useful clues for unraveling the biotechnological potential of this species for lignocellulosic biorefinery.